Hubungan Sarapan Pagi dengan Status Gizi Anak Sekolah Kelas 5 di SD Tunas Bangsa Denpasar Tahun 2024 - Chelsy Tihonksky; I Made Purnadhibrata; Vera Vera (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Breakfast is often considered an important habit to support health and nutritional status in school children. This study aimed to determine whether there is a correlation between breakfast and the nutritional status of 5th grade at SD Tunas Bangsa Denpasar in 2024. The research used a quantitative design with a cross-sectional approach. The sample consisted of 35 students selected through total sampling. Data were collected using questionnaires and anthropometric measurements (BMI-for-age). The analysis revealed that although most students who regularly had breakfast maintained good nutritional status, the Spearman test showed no significant relationship between breakfast habits and nutritional status (p-value > 0.05). This study concludes that breakfast does not have a direct relationship with nutritional status, although it remains important as part of a healthy lifestyle.